Efficacy and tolerability of budesonide/formoterol added to tiotropium compared with tiotropium alone in patients with severe or very severe COPD: A randomized, multicentre study in East Asia. Issue 1 (23rd September 2015) - Lee, Sang‐Do; Xie, Can‐mao; Yunus, Faisal; Itoh, Yohji; Ling, Xia; Yu, Wai‐cho; Kiatboonsri, Sumalee
Abstract: Background and objective: Triple combination therapy with tiotropium plus budesonide/formoterol has improved lung function and reduced exacerbation risk in patients with chronic obstructive pulmonary disease (COPD) in Western countries, but no such data exist for East Asian patients. This study aimed to evaluate the efficacy and tolerability of adding budesonide/formoterol to tiotropium compared with tiotropium alone in East Asian patients with severe/very severe COPD. Methods: This 12‐week, randomized, parallel‐group, multicentre, open‐label study was conducted in East Asia. After a 14‐day run‐in period during which patients received tiotropium 18 μg once daily, patients were randomized to tiotropium (18 μg once daily) + budesonide/formoterol (160/4.5 μg 2 inhalations twice daily) or tiotropium alone (18 μg once daily). The primary endpoint was change from baseline in pre‐dose forced expiratory volume in 1 s (FEV1 ) to the mean of values measured at Weeks 1, 6 and 12. Results: Pre‐dose FEV1 significantly increased from baseline with tiotropium plus budesonide/formoterol ( n = 287) versus tiotropium alone ( n = 291) (5.0% vs 0.6%; treatment difference: 4.4% (95% CI: 1.9–6.9), P = 0.0004). Triple therapy also reduced the COPD exacerbation rate by 40.7% ( P = 0.0032) and prolonged time to first exacerbation (38.6% risk reduction, P = 0.0167) versus tiotropium alone and markedly improved health‐related quality of life (HRQoL), measured using the St George's Respiratory Questionnaire. Incidence of adverse events was 26% for both groups. Conclusions: In East Asian patients with severe/very severe COPD, adding budesonide/formoterol to tiotropium was associated with significant improvements in FEV1 and HRQoL and lower COPD exacerbation rates. Treatment was generally well tolerated. Clinical trial registration:NCT01397890 at Clinicaltrials.gov Abstract : The effects of adding ICS/LABA (budesonide/formoterol) therapy to tiotropium therapy in East Asian patients with severe and very severe COPD were assessed in this randomized phase IV study. This is the first study to assess the effects of budesonide/formoterol in addition to tiotropium in this patient group.